Why publishing the Journal of Public Health in Africa - Vittorio Colizzi; Nelson Sonela (AOSIS, 2017)
The population of sub-Saharan Africa faces global health challenges more than any other part of the world, bearing the brunt of tuberculosis, malaria and HIV/AIDS. This region already carries 24% of the global disease burden and the situation is made worst by the advent of noncommunicable diseases, such as coronary heart disease, hypertension, cancer and diabetes (just to name a few). Thus the need for African scientists to disseminate research data in order to alleviate the continent's huge disease burden and help the frail health systems affected by poverty, underdevelopment, conflicts and poorly managed government agencies. In our opinion, the Journal of Public Health in Africa responds to the need for a communication system aimed at reaching the widest audience of professionals worldwide in a shorter time than traditional publishing [...]